An overview of perioperative considerations in elderly patients for thoracic surgery: demographics, risk/benefit, and resource planning. Issue 1 (February 2018) - Castillo, Maria
Abstract : Purpose of review: Increasing numbers of geriatric patients will present for thoracic surgery as the population ages. The changes in physiologic reserve as well as the increase in comorbid conditions among this population must be considered in order to optimize patient care in the perioperative period. Recent findings: For elderly patients with cancer, the risk–benefit relationship for thoracic surgery remains favorable. Consideration of comorbidities, especially chronic obstructive pulmonary disease and congestive heart failure, is important in the setting of surgical treatment, as they have implications for perioperative care as well as postoperative morbidity and mortality. Overall survival, quality of life, and health status must be considered in decisions regarding cancer treatment. Summary: Elderly patients with early-stage lung cancer derive benefit from surgical treatment, despite their increased prevalence of comorbidities, because survival associated with untreated lung cancer is so dismal. Some studies suggest that even late-stage lung cancer patients may benefit from surgery as part of a multimodal approach. Further studies could help target implementation of resources to optimize overall patient health and physiologic condition in order to decrease morbidity and mortality and to optimize quality of life.